Juvenile Reoffending: a ten‐year retrospective cohort analysis. Issue 4 (December 2015) - Payne, Jason; Weatherburn, Don
Abstract : Criminologists and other developmental researchers have long acknowledged the importance of both continuity and change in antisocial and criminal behaviour over the life‐course. To the extent that young offenders having contact with the police will persist with offending into adulthood is an important social issue with significant implications for the ongoing development and implementation of early intervention and prevention programs. Using data from New South Wales, this paper tracks a cohort of 8, 797 juvenile offenders over ten years and is among the first of its kind to use multivariate techniques to examine the long‐term outcomes of those who were cautioned, conferenced or convicted in that state. The study finds that just over half of all juvenile offenders were reconvicted in court of a further offence and that reconviction rates were higher for young males and Indigenous offenders than for females or non‐Indigneous offenders. In concluding, this paper draws attention to the need for improved assessment and early intervention efforts that more accurately target those young people most at risk of persisting with offending into adulthood.